Peningkatan Hasil Belajar Matematika Materi Bangun Datar Kelas 1 Dengan Menggunakan Model Pembelajaran Project-Based Learning Di SD Negeri 1 Kalikotes - Widayati, Genda (Universitas Sebelas Maret, 2022)
Educators can improve student learning outcomes by varying learning and must be able to provide innovation in learning, such as in selecting the learning model to be used. The aim of carrying out this research is to improve learning outcomes in mathematics subjects with plane material using a project-based learning model in class 1 of SD Negeri 1 Kalikotes. The research method used in this research is classroom action research (PTK). With research subjects 10 grade 1 students at SD Negeri 1 Kalikotes. This research stage uses 3 stages, namely pre- cycle, cycle 1 and cycle 2 with 2 meetings in each cycle. The results of the research state that: by implementing the project-based learning model, it can improve student learning outcomes in mathematics learning about plane shapes with a pre-cycle KKM pass percentage of 50%, cycle 1 64% and cycle 2 87%.